Why It Is Necessary to Use the Entire Root rather than Partial Root When Doing Contralateral C7 Nerve Transfer: Cortical Plasticity Also Matters besides the Amount of Nerve Fibers. (5th January 2021) - Guo, Jinding; Zhao, Xin; Lao, Jie; Gao, Kaiming
Abstract : Previous studies suggested that the mode of donor transection is a critical factor affecting the efficacy of the contralateral C7 (CC7) nerve transfer. Nevertheless, the mechanism underlying this phenomenon remains elusive. The aim of this study was to investigate the relationship between the division modes of the CC7 nerve and cortical functional reorganization of Sprague-Dawley rats. We hypothesized that different methods of CC7 nerve transection might induce differences in cortical functional reorganization, thus resulting in differences in surgery efficacy. BDNF, TNF- α /IL-6, and miR-132/134 were selected as indicators of cortical functional reorganization. No significant differences in all these indicators were noted between the entire group and the entire root+posterior division group (P > 0.05 ). BDNF and miR-132/134 levels in the entire group and the entire root+posterior division group were significantly increased compared with their levels in the posterior group and the blank control group (P < 0.001 ). In all groups, BDNF, TNF- α /IL-6, and miR-132/134 levels in both hemispheres initially increased and subsequently decreased until week 40. In conclusion, this study provided the evidence of dynamic changes in BDNF, TNF- α /IL-6, and miR-132/134 in the cortex of rats after CC7 nerve transfer using different transecting modes, demonstrating that different CC7 nerve divisions might result in different surgical effects through modulation of cortical reorganization.